Perancangan Media Pembelajaran Biologi Kelas XI ‎Berbasis Android Menggunakan Ispring Suite 10 di SMAN ‎‎1 Banuhampu - Sasti, Tiara ‎; Derta, Sarwo; Musril, Hari Antoni; Okra, Riri (ANTHOR: Education and Learning Journal, 2022)
The background of this research is that Biology teachers in class XI use conventional media such as books and blackboards in teaching, this is certainly not in accordance with the demands of technological developments, causing students to become bored and less interested in learning. The purpose of this research is to produce an Android-based Biology learning media for Class XI using Ispring Suite 10 at SMAN 1 Banuhampu as additional media. This study uses the Vaughan version of the media development model, namelyplanning and financing, design and production, testing, and delivery. of the four stages thenuse Blackbox. The product test results in this study obtained a value of 0.81 and 0.83, thenthe validity of the linguistic aspect obtained a value of 0.95 and a material aspect validityvalue of 0.9 in the Valid criteria. The practicality value is 0.90 on the Very High criteria. And the Effectiveness Value is 0.77 in the High Effectiveness criteria. So that the media used can be additional media in learning.